PELATIHAN PENGGUNAAN APLIKASI MENDELEY: CARA MUDAH MENGELOLA REFERENSI ILMIAH DI STIKES MEDIKA SERAMOE BARAT - Hilma Erliana; Rahmad Nuthihar; Luthfi Luthfi; Riza Hasan; Safrizal Safrizal (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The Mendeley application makes it very easy for authors to cite reference sources and write a bibliography accurately and quickly according to the specified bibliography style. This service activity trains students to use the Mendeley application for scientific paper writing. This service was conducted at Medical College of Health (STIKES) West Seramoe. The target group of this service are students. The selection of this service point was based on the results of interviews with students from STIKES Medika West Seramoe, most of whom compiled a bibliography manually. The method of conducting community service is carried out in the phases of (1) preparing for community service activities and (2) conducting community service activities. Learning and practicing this service involves the following steps: (1) Installing the Mendeley application; (2) operate Mendeley; (3) add references; (4) Add reference files automatically; (5) perform citations; and (6) compiling a bibliography. The results of conducting for this service allow the conclusion that students can operate the Mendeley application well. Mendeley operations helps students with citation/quotes by using Mendeley correctly in scientific reports.